Genetic variations of IL-12B, IL-12Rβ1, IL-12Rβ2 in Behcet's disease and VKH syndrome. - Xinyu Li (Public Library of Science (PLoS), 2014)
Purpose To investigate the associations of single nucleotide polymorphisms (SNPs) of three genes (IL-12B, IL-12Rβ1 and IL-12Rβ2) in Behcet's disease (BD) and Vogt-Koyanagi-Harada (VKH) syndrome in a Chinese Han population. Methods A total of 806 BD cases, 820 VKH patients, and 1600 healthy controls were involved in this study. The first investigation included 400 BD patients, 400 VKH cases, and 600 healthy individuals. A second confirmatory study included a separate set of 406 BD patients, 420 VKH cases and another 1000 normal controls. Genotyping was carried out by PCR-restriction fragment length polymorphism assay and results were validated by using direct sequencing. The χ2 test was performed to compare the allele and genotype frequencies between cases and healthy controls. Results This study comprised two phases. In the first phase study, a significantly increased frequency of the rs3212227/IL-12B genotype CC and C allele was found in BD patients as compared to controls (Bonferroni corrected p value (pc) = 0.009, OR 1.8; pc = 0.024, OR 1.3, respectively). Moreover, the frequency of the C allele of rs3212227/IL-12B was also significantly increased in VKH patients (pc = 0.012, OR 1.3, 95% CI 1.1 to 1.6). No associations were found for the other seven tested SNPs either in BD or VKH disease. The second study as well as the combined data confirmed the significant association of rs3212227/IL-12B with BD (CC genotype: combined pc = 6.3×10(-7), OR = 1.8; C allele: combined pc = 2.0×10(-5), OR = 1.3, respectively) and the C allele frequency of rs3212227/IL-12B as the risk factor to VKH patients (combined pc = 2.5×10(-5), OR 1.3, 95% CI 1.2 to 1.5). Conclusions Our study revealed that the IL-12B gene is involved both in the susceptibility to BD as well as VKH syndrome.